TAGMEMICS ANALYSIS - Dewi, Ariviani (MAJALAH ILMIAH GEMA, 2012)
Tagmemic is not as popular as other theory but it is a branch of linguistic. The constructor is Kenneth Lee Pike who developed the theory in 1930s. He focuses on the form of language thus it is the offshoot of structuralism. He connects his theory with etic and emic and calls the minimal grammatical unit of (emic) meaning a grameme but later changes into tagmeme. He also highlights the goal of tagmemic inquiry which is a movement toward an emic understanding of a text.  Pike’s fundamental unit of language falls into four features; slot, class, role, and cohesion. He formulates the analysis of tagmemic into four categories; at sentence level, clause level, phrase level, word level, and morpheme level. Since Tagmemic concerned with the form, so it is applicable to any language but remained left several disadvantages as well. Key words: tagmemic, emic and etic, slot, class, role, cohesion, sentence level, phrases level, word level, morpheme level.